Exosomes: efficient macrophage-related immunomodulators in chronic lung diseases - Kang, Jianxiong; Hua, Peiyan; Wu, Xiaojing; Wang, Bin (Frontiers in Cell and Developmental Biology, 2024)
Macrophages, the predominant immune cells in the lungs, play a pivotal role in maintaining the delicate balance of the pulmonary immune microenvironment. However, in chronic inflammatory lung diseases and lung cancer, macrophage phenotypes undergo distinct transitions, with M1-predominant macrophages promoting inflammatory damage and M2-predominant macrophages fostering cancer progression. Exosomes, as critical mediators of intercellular signaling and substance exchange, participate in pathological reshaping of macrophages during development of pulmonary inflammatory diseases and lung cancer. Specifically, in inflammatory lung diseases, exosomes promote the pro-inflammatory phenotype of macrophages, suppress the anti-inflammatory phenotype, and subsequently, exosomes released by reshaped macrophages further exacerbate inflammatory damage. In cancer, exosomes promote pro-tumor tumor-associated macrophages (TAMs); inhibit anti-tumor TAMs; and exosomes released by TAMs further enhance tumor proliferation, metastasis, and resistance to chemotherapy. Simultaneously, exosomes exhibit a dual role, holding the potential to transmit immune-modulating molecules and load therapeutic agents and offering prospects for restoring immune dysregulation in macrophages during chronic inflammatory lung diseases and lung cancer. In chronic inflammatory lung diseases, this is manifested by exosomes reshaping anti-inflammatory macrophages, inhibiting pro-inflammatory macrophages, and alleviating inflammatory damage post-reshaping. In lung cancer, exosomes reshape anti-tumor macrophages, inhibit pro-tumor macrophages, and reshaped macrophages secrete exosomes that suppress lung cancer development. Looking ahead, efficient and targeted exosome-based therapies may emerge as a promising direction for treatment of pulmonary diseases.